Phonocardiographic method of assessing changes in left ventricular function after Starr-Edwards replacement of aortic valve - Gibson, D. G. (1970)
A phonocardiographic method is described for measuring the time taken by the ball of a Starr-Edwards prosthesis to move to the apex of the cage at the onset of left ventricular ejection, and from this its acceleration can be derived. The acceleration is conspicuously increased in post-ectopic beats and in exercise, but is unaffected by posture and tachycardia induced by atropine or ventricular pacing. It is suggested that the acceleration of the ball is related to the initial acceleration of blood into the ascending aorta.